Primary bliary crrhosis in pregnancy - Olga Adamczyk-Gruszka; Izabela Lewandowska-Andruszuk; Marzena Wrześniewska; Jakub Gruszka; Karolina Komar-Gruszka (Kazimierz Wielki University, 2018)
Introduction Primary biliary cirrhosis (PBC) is a chronic hepatic condition presumably of immune etiology. In genetically predisposed patients, progressing immunization of the liver is stimulated by environmental or infectious agents. As a result of ill-targeted immune response antimitochondrial autoantibodies M2 (AMA-M2) are produced. They slowly damage fine intrahepatic biliary ducts with typical inflammatory response and subsequent cholestasis, often progressing to hepatic cirrhosis and liver failure, and if it has reached 4 stage, primary hepatic cancer. PBC is most frequently diagnosed in women after the age of 30. It is 13 times more frequent in females than in males. Currently, PBC is often diagnosed at the asymptomatic stage or when nonspecific symptoms have developed, i.e. fatigue or pruritus. Biochemical tests present elevated cholestatic markers, and immune tests detect elevated autoimmune antibodies AMA and IgM. In advanced cases of hepatic cirrhosis, liver transplant is considered as a final treatment. Case study The patient, a 31-year old woman, CI PI, with PBC was first seen in 7 hbd. Her medical history revealed PBC had been diagnosed a year earlier. First clinical symptoms occurred 5 years ago, treated with Proursan. The patient was hospitalized 5 times, i.e. in 30, 36, 37, 38 and 39 hbd, among others, for threatening preterm delivery and cholestasis, and later for liver dysfunction associated with PBC, and for labor. In 39 hbd delivery was induced, and she gave birth (naturally) to a live neonate, female, weighing 2,830g, body length 52 cm, Apgar score 9-10. The liver function improved after the delivery and stabilized. The patient is followed up, treatment with Proursan continued. Pregnancy in patients with PBC is associated with mother's exacerbated condition, especially in the third trimester and puerperium. The aforementioned case study shows that with proper care successful management and termination of pregnancy is safe for both mother and her baby.